Bangladesh : World Bank Country-Level Engagement on Governance and Anticorruption - Wescott, Clay; Breeding, Mary (World Bank, Washington, DC, 2017)
Bangladesh is one of the world's poorest and most densely populated countries, and subject to annual cyclones and flooding. Despite these challenges, it benefits from strong economic growth, good performance on health and education, and poverty reduction, alongside weak governance and pervasive corruption. The reasons include strong macroeconomic policy, pro-poor spending, credible elections, export growth and remittances, improved capacity for managing natural disasters, and a stronger civil society than comparable countries. After over a decade of intense engagement with the Bank on governance, Bangladesh adopted in 2006 a governance-oriented Country Assistance Strategy (CAS) with four main objectives: to improve implementation capacity; to 'tackle corruption' by fully operationalizing the Anti-Corruption Commission; to lay the foundation for comprehensive legal and judicial reform; and to strengthen 'voice, empowerment and participation.' The choice of a wide range of instruments and areas of intervention was appropriate, given the political instability at the time of 2006 CAS preparation. The Bank signaled it was ready to engage in all areas, and could scale up or pull back depending on emerging political and bureaucratic commitment. The 2006 CAS yielded mixed results, and the subsequent Country Partnership Strategy (CPS) has been more selective on GAC issues. At the project level, governance has been a key priority, in line with the South Asia region's heavy emphasis on GAC-in-Projects. Investments in GAC-in-primary education, a local government project, anti-corruption efforts in the power sector, and projects strengthening the investment climate have yielded positive results. Investments in GAC-in-roads projects have had mixed results in terms of effectiveness. GAC activities were mainly adopted prior to the 2007 GAC strategy. Although Bangladesh was a Country Governance and Anticorruption (CGAC) country, the country team chose not to use CGAC funds because the country had already been intensively using GAC approaches well before the GAC strategy was adopted.